Optimum Drop Jump Height in Division III Athletes: Under 75% of Vertical Jump Height - Peng, Hsien-Te; Khuat, Cong Toai; Kernozek, Thomas W.; Wallace, Brian J.; Lo, Shin-Liang; Song, Chen-Yi (International Journal of Sports Medicine, 2017)
Our purpose was to evaluate the vertical ground reaction force, impulse, moments and powers of hip, knee and ankle joints, contact time, and jump height when performing a drop jump from different drop heights based on the percentage of a performer’s maximum vertical jump height (MVJH). Fifteen male Division III athletes participated voluntarily. Eleven synchronized cameras and two force platforms were used to collect data. One-way repeated-measures analysis of variance tests were used to examine the differences between drop heights. The maximum hip, knee and ankle power absorption during 125%MVJH and 150%MVJH were greater than those during 75%MVJH. The impulse during landing at 100%MVJH, 125%MVJH and 150%MVJH were greater than 75%MVJH. The vertical ground reaction force during 150%MVJH was greater than 50%MVJH, 75%MVJH and 100%MVJH. Drop height below 75%MVJH had the most merits for increasing joint power output while having a lower impact force, impulse and joint power absorption. Drop height of 150%MVJH may not be desirable as a high-intensity stimulus due to the much greater impact force, increasing the risk of injury, without increasing jump height performance.
Keywords: kinematics; kinetics plyometric exercise; inverse dynamics; stretch shortening cycle